PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP HASIL BELAJAR SHOOTING SEPAKBOLA (STUDI PADA SISWA KELAS VIII SMP NEGERI 1 KEDIRI) - ADHI SUROYO, BIJAK (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Learning model is one of the keys to success in teaching and learning activities. In the presentation the teacher can take a variety of approaches or learning model that aims to make the students gain an understanding and better absorbed information so that the learning process can be done optimally. Learning model chosen should have to conform to the conditions of the school and the student's ability as a whole. For it is given the appropriate learning innovation with the background. Provision of learning innovation in question is the provision of cooperative learning model Student Teams Achievement Division (STAD) in the learning of shooting football. Expected with this model provision would indicate that maximum learning outcomes. This study aimed to determine the effect of cooperative learning model Student Teams Achievement Division (STAD) on learning outcomes of shooting football. This research is descriptive quantitative approach to experiment with. The sample in this study amounted to 62 students, which consisted of 31 students of class VIII F as the experimental group and 31 students of class VIII D as a control group. From the results of statistical calculations it can be concluded that there is a significant effect of cooperative learning model Student Teams Achievement Division (STAD) on learning outcomes as evidenced shooting football from t_hitung value (4.488)> t??_tabel (2.042) with a significance level of 0.05. While the greatest effect is found to be 30.13%. Keywords: STAD Cooperative Learning, Shooting Football, Learning Outcomes